ANALYSIS OF EFFECTIVENESS ASSESSMENT CRITERIA OF FREE ECONOMIC ZONES IN DIGITAL ECONOMY CONDITIONS - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: This article examines the analysis of the criteria for assessing the effectiveness of free economic zones in the digital economy. The development of criteria for assessing the activities of free economic zones serves as a basis for stimulating their development. Based on world experience, it is important for the development of countries and regions to identify indicators of the effective functioning of free economic zones, pay attention to their analysis, and based on this, select the most appropriate methods of attracting investors. The article also highlights the importance of analyzing indicators, experiences and implementing them in this process.